Kesztölc: population and settlement morphology - Nyírő , András (Studia Mundi – Economica, 2019)
Kesztölc retained its medieval structure until the 17th century. Because of the terrain, the settlement was expanded in the western direction. During the Industrial Revolution, the number of populations has begun to increase. Then the classical one-way morphology came to its notice. After the Second World War, the growth of the population of the village fell. In the TSZ era, the houses of the Ujfalu were built and the former one-way structure was transformed. After 1989, the suburbs of the eastern border of the village developed.